The quest for the real Jesus : Radboud Prestige lectures by Prof. Dr. Michael Wolter. - Watt, Jan van der. (Biblical Interpretation Series, 2013)
The Radboud Prestige Lectures in New Testament 2010 were presented by Prof. Michael Wolter (University of Bonn). His prestige lecture was entitled: 'Which is the real Jesus?'. In this lecture he challenged many of the current views within the historical Jesus research by critically evaluating the approaches in various categories. Afterwards this lecture was presented to a variety of scholars from different disciplines who approach the problem from their particular perspectives, thus bringing a rich texture of insights, apart from engaging critically with Wolter's views. Thus one can appreciate the role the quest for the historical Jesus plays within a wider framework. This resulted in interesting articles that not only deal with historical, but also with philosophical and hermeneutical issues.